Processes used by managers to acquire skills, knowledge and attitudes - Butcher, Carol Anne (My University, 1999)
This research report investigates the processes used by middle managers to acquire skills, knowledge and attitudes. An understanding of the processes that best develops each of these is important since each has an impact on managerial effectiveness. The literature review revealed that very little research has been undertaken to discover how middle managers acquire these necessary abilities to become effective managers. The research methodology comprised the self-completion of questionnaires. The sample consisted of 111 respondents, all of whom had at least two years experience in middle management. The. respondents were all students currently studying at the Wits Business School. Respondents rated various training techniques and learning styles and indicated whether each best developed skills, knowledge or attitudes. Quantitative data analysis such as two variable chi square tests, frequency distributions, means, and modes were used. The results revealed that skills, knowledge and attitudes are acquired differently. Furthermore, the research revealed that sector and gender did not influence the learning methods. A list of best practices for the development of skills, knowledge and attitudes was developed.
A research report submitted to the Faculty of Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements of the degree of Master of Management, Johannesburg (February, 1999)
Keywords: Executive ability